Islam Dan Studi Agama-Agama: Telaah Atas Buku Approaches To Islam In Religious Studies Karya Ricard C. Martins - Rubi Babullah; Yurna Yurna; Siti Ulfah Fauziah; Ujang Nata Direja; Neneng Nur (Concept: Journal of Social Humanities and Education, 2023)
Islam gained great attention in the study of religion due to the development and global influence on the world Muslim population. An understanding of Islam as a religion and understanding of religion from the viewpoint of Islam is an issue that needs to be elaborated in the discussion and the discussion in the field of religious studies. The failure of religious studies to standardize itself as a 'discipline', although many emerging religious studies. The position of those who want to ask "how" to learn Islam as a religion perplexed by tendencies on compartmentalization in education. The failure of religious studies to standardize itself as a scientific discipline, but the outlook is promising because someday they may be separate disciplines by seeking consensus regarding curriculum, problem solving, and performance criteria and become academic background. From a more narrow academic context, so any problem that arises is the study of religion as a whole.